Performance of broiler chicken under cage and floor systems of management fed differently processed feeds* - VANAN, THANGA THAMIL; THIAGARAJAN, M; RAMESH, V; GNANARAJ, P TENZING; SIVAKUMAR, T (The Indian Journal of Animal Sciences, 2014)
An experiment was carried out to find out the performance of broiler chicken fed 3 differently processed feeds namely untreated, UV rays exposed and UV rays ± microwave exposed under cage and floor systems of management. Eight trials were conducted covering 4 seasons namely hot, Southwest monsoon, Northeast monsoon and Moderate. A floor space of 450 cm2 and 900 cm2 / bird was allotted in cage and litter systems respectively. For each trial 120, day-old Vencob unsexed chicks belonging to the same hatch were used. They were allotted at random and subjected to control-fed with broiler mash, mash irradiated with UV rays in the intensity of 80 W/cm2 at 253.7 nm for 5 min and fed with UV rays irradiated mash processed in microwave power of 1200 W at 2450 MHZ for 5 min under cage and floor systems respectively. From the results of this study it was inferred that the cage system of rearing could be adopted for commercial broiler rearing due to better growth rate, feed efficiency, survival rate and carcass quality. When cage reared ch.icks fed with UV rays irradiated mash, it resulted in significantly (P<0.01) higher weight gain of 1.738 kg at seventh week of age, with the cost of production of Rs 30.25 ± 1.5 and the best economy index of 1.8 ± 0.32 .